2022
DOI: 10.1002/lno.12224
|View full text |Cite
|
Sign up to set email alerts
|

Examining ecological succession of diatoms in California Current System cyclonic mesoscale eddies

Abstract: The California Current System is a diatom-dominated region characterized by seasonal coastal upwelling and additional elevated mesoscale activity. Cyclonic mesoscale eddies in the region trap productive coastal waters with their planktonic communities and transport them offshore with limited interaction with surrounding waters, effectively acting as natural mesocosms, where phytoplankton populations undergo ecological succession as eddies age. This study examines diatom community composition within two mesosca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…This process depends heavily on nutrient and light availability, which are significantly influenced by physical processes such as mixing and meso-/submeso-scale dynamics (Mahadevan, 2016;McGillicuddy, 2016). Oceanic mesoscale eddies can effectively facilitate phytoplankton growth by heaving isopycnal surfaces upward into euphotic zone (McGillicuddy et al, 1998), as found by in situ observations (Abdala et al, 2022;Benitez-Nelson et al, 2007;Brown et al, 2008;Cornec et al, 2021;Huang & Xu, 2018;Morán et al, 2001;Xiu & Chai, 2020;Zhou et al, 2021). In addition, recent studies have highlighted the significant impact of frontal submesoscale physics on transporting deep nutrients into the sunlit layer, which promotes phytoplankton growth (Chen et al, 2022;Hosegood et al, 2017;Lévy et al, 2018;Liu & Levine, 2016;Mahadevan, 2016).…”
Section: Introductionmentioning
confidence: 95%
“…This process depends heavily on nutrient and light availability, which are significantly influenced by physical processes such as mixing and meso-/submeso-scale dynamics (Mahadevan, 2016;McGillicuddy, 2016). Oceanic mesoscale eddies can effectively facilitate phytoplankton growth by heaving isopycnal surfaces upward into euphotic zone (McGillicuddy et al, 1998), as found by in situ observations (Abdala et al, 2022;Benitez-Nelson et al, 2007;Brown et al, 2008;Cornec et al, 2021;Huang & Xu, 2018;Morán et al, 2001;Xiu & Chai, 2020;Zhou et al, 2021). In addition, recent studies have highlighted the significant impact of frontal submesoscale physics on transporting deep nutrients into the sunlit layer, which promotes phytoplankton growth (Chen et al, 2022;Hosegood et al, 2017;Lévy et al, 2018;Liu & Levine, 2016;Mahadevan, 2016).…”
Section: Introductionmentioning
confidence: 95%